2005
DOI: 10.1016/j.pbb.2005.06.005
|View full text |Cite
|
Sign up to set email alerts
|

The airway sensory impact of nicotine contributes to the conditioned reinforcing effects of individual puffs from cigarettes

Abstract: Puffs from cigarettes are the fundamental unit of smoking reward. Here, we examined the extent to which reward from puffs can be derived from the airway sensory effect of nicotine, in the absence of a direct central nervous system effect of nicotine. We did this by assessing the self-reported reward obtained from individual puffs from nicotinized, denicotinized and unlit cigarettes within 7 s of inhalation, which is before nicotine had an opportunity to reach the brain. We also assessed the self-reported stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(33 citation statements)
references
References 48 publications
2
31
0
Order By: Relevance
“…In tobacco-dependent smokers, smoking denicotinized cigarettes has been found to result in a degree of withdrawal relief that is similar to smoking regular cigarettes (Pickworth et al, 1999;Buchhalter et al, 2001;Dallery et al, 2003;Donny et al, 2007); however, denicotinized cigarettes provide less satisfaction (Butschky et al, 1995;Gross et al, 1997), reward (Naqvi and Bechara, 2005;Donny et al, 2007), and anxiety reduction (Pomerleau et al, 1984;Buckley et al, 2007) than regular cigarettes. Denicotinized cigarettes also do not elevate heart rate like regular cigarettes (Butschky et al, 1995;Pickworth et al, 1999;Schuh et al, 2001;Buchhalter et al, 2001), but both cigarette types increase skin conductance responses (Naqvi and Bechara, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tobacco-dependent smokers, smoking denicotinized cigarettes has been found to result in a degree of withdrawal relief that is similar to smoking regular cigarettes (Pickworth et al, 1999;Buchhalter et al, 2001;Dallery et al, 2003;Donny et al, 2007); however, denicotinized cigarettes provide less satisfaction (Butschky et al, 1995;Gross et al, 1997), reward (Naqvi and Bechara, 2005;Donny et al, 2007), and anxiety reduction (Pomerleau et al, 1984;Buckley et al, 2007) than regular cigarettes. Denicotinized cigarettes also do not elevate heart rate like regular cigarettes (Butschky et al, 1995;Pickworth et al, 1999;Schuh et al, 2001;Buchhalter et al, 2001), but both cigarette types increase skin conductance responses (Naqvi and Bechara, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Denicotinized cigarettes also do not elevate heart rate like regular cigarettes (Butschky et al, 1995;Pickworth et al, 1999;Schuh et al, 2001;Buchhalter et al, 2001), but both cigarette types increase skin conductance responses (Naqvi and Bechara, 2006). Furthermore, a recent study directly demonstrated that the airway sensation from nicotinized cigarette puffs were more rewarding than such sensations from denicotinized cigarette puffs (though both cigarette types produced greater reward than unlit puffs) (Naqvi and Bechara, 2005). Taken together, these studies indicate that sensory factors associated with smoking are important for relief of withdrawal, but that nicotine may be necessary for the rewarding properties of smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Work by others (Pritchard et al, 1996;Rose et al, 1999) has shown that nicotine's airway sensory effects are a source of hedonic impact from smoking. An earlier study by our laboratory (Naqvi and Bechara, 2005) in which hedonic impact was assessed before nicotine reached the brain showed that nicotinized puffs elicit more hedonic impact than denicotinized puffs in large measure because nicotinized puffs stimulate more intense airway sensations than denicotinized puffs. Though one cannot exclude the contribution of nicotine's pharmacologic (i.e.…”
Section: Within-subject Differences In Scr Between Nicotinized Denicmentioning
confidence: 98%
“…Recent smoking may also have acted to reduce the pharmacologic effects of nicotine from individual puffs as a result of acute tolerance, which lasts for up to 2 h following nicotine exposure (Perkins et al, 1995). Previous results (Naqvi and Bechara, 2005) have shown that, despite a diminished pharmacologic effect of nicotine due to recent smoking, nicotine still exerts airway sensory effects.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation